Addressing the challenging behavior of children with high functioning autism/Asperger syndrome in the classroom : a guide for teachers and parents - Moyes, Rebecca A. (Rebecca Ann), 1960- (Jessica Kingsley, 2002)
How do teachers and parents of children with autism address a child's social skills? And what do they do about problem behaviors? This book provides possible explanations for these behaviours, and a wealth of practical help for both teachers and parents to address them. Teachers learn how to create environmental supports and how to incorporate specific teaching strategies. Students with autism learn the new skills they might need, and ways of making their behavior more acceptable. This book is full of practical tips on how to tackle different kinds of challenging behaviors both in the classroom and outside it.